2008
DOI: 10.1590/s0074-02762008000200009
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and antigenic characterization of influenza viruses isolated in Curitiba, South Brazil

Abstract: Several studies conducted all over the world have reported that the influenza virus is associated with great morbidity and mortality rates. In this study, we analyzed the incidence of the influenza virus between 2000 and 2003 in Curitiba. We studied 1621 samples obtained from outpatients and hospitalized patients of both sexes and all ages. The study was conducted at the local primary care health units (outpatients) and at the tertiary care unit (hospitalized) of the General Hospital of the Federal University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…We detected influenza in 19.1% of the samples from the two groups of patients, which is in agreement with other Brazilian studies that have reported influenza A and B viruses as important causes of respiratory viral disease in immunocompromised and pediatric patients (9,10). The incidence of influenza infection among HSCT recipients is variable and is related to influenza epidemics in addition to the prevention measures adopted by each center.…”
Section: Discussionsupporting
confidence: 92%
“…We detected influenza in 19.1% of the samples from the two groups of patients, which is in agreement with other Brazilian studies that have reported influenza A and B viruses as important causes of respiratory viral disease in immunocompromised and pediatric patients (9,10). The incidence of influenza infection among HSCT recipients is variable and is related to influenza epidemics in addition to the prevention measures adopted by each center.…”
Section: Discussionsupporting
confidence: 92%
“…The death and hospitalisation rates varied in all countries (WHO 2009a). Morbidity and mortality resulting from seasonal influenza and other respiratory viruses have long been described in the country (Straliotto et al 2002, Bellei et al 2007, Vidal et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…In all, 12 articles presenting evidence on influenza B virus circulation in Brazil for the years 1996-2013 were included. [30][31][32][33][34][35][36][37][38][39][40][41] Details for each of the studies are shown in Supplementary File 1.…”
Section: Online Literature Searchmentioning
confidence: 99%